Dalbavancin treatment for prosthetic joint infections in real-life: a national cohort study and literature review. (June 2021) - Matt, Morgan; Duran, Clara; Courjon, Johan; Lotte, Romain; Moing, Vincent Le; Monnin, Boris; Pavese, Patricia; Chavanet, Pascal; Khatchatourian, Lydie; Tattevin, Pierre; Cattoir, Vincent; Lechiche, Catherine; et al.
Highlights: Dalbavancin is effective for treatment of prosthetic joint infections (PJIs). Dalbavancin is a safe and easy treatment for PJIs. The optimal dosage regimen needs to be defined. ABSTRACT: Objectives: Dalbavancin is a long-lasting lipoglycopeptide active against Gram-positive bacteria, especially methicillin-resistant staphylococci. Few data are available on dalbavancin use for treatment of prosthetic joint infections (PJIs). We describe a cohort of patients treated for PJI with dalbavancin and review the literature regarding this condition. Methods: All adult patients with PJI from the French dalbavancin national cohort from 1 June 2017 to 1 January 2019 were included. We collected clinical and microbiological characteristics and outcome through a standardised questionnaire. Clinical cure was defined as absence of clinical signs of infection at last visit. Failure was a composite criterion defined by persistence or reappearance of signs of infection, and/or switch to suppressive antibiotic treatment and/or death from infection. The literature review was performed using PubMed. Results: Seventeen patients were included. Bacteria were identified in 16 cases: Staphylococcus aureus ( n  = 10), including methicillin-resistant S. aureus ( n  = 1); and coagulase-negative staphylococci ( n  = 10), including methicillin-resistant Staphylococcus epidermidis ( n  = 4). Sixteen patients (94.1%) had received antibiotic therapy prior to dalbavancin use (mean of 2.2 ± 1.3 lines). Clinical cure was achieved in 8/17 patients after a median follow-up of 299.0 (IQR 97.0–476.0) days. We reviewed all cases of PJI treated with dalbavancin available in the literature and the overall clinical cure was estimated at 73.1%. Conclusion: Our study and literature data suggest that use of dalbavancin in PJI could be considered, even as salvage therapy. Dalbavancin appears to be a safe and easy treatment for patients with staphylococcal PJIs.